Zi Shen Wan Fang repaired blood–brain barrier integrity in diabetic cognitive impairment mice via preventing cerebrovascular cells senescence - Qingsheng Yin; Genhui Yang; Runtao Su; Jie Bu; Ying Li; Han Zhang; Yanjun Zhang; Pengwei Zhuang (Chinese Medicine)
Abstract Background Blood–brain barrier (BBB) integrity disruption is a key pathological link of diabetes-induced cognitive impairment (DCI), but the detailed mechanism of how the diabetic environment induces BBB integrity disruption is not fully understood. Our previous study found that Zi Shen Wan Fang (ZSWF), an optimized prescription consisting of Anemarrhenae Rhizoma (Anemarrhena asphodeloides Bge.), Phellodendri Chinensis Cortex (Phellodendron chinense Schneid.) and Cistanches Herba (Cistanche deserticola Y.C.Ma) has excellent efficacy in alleviating DCI, however, whether its mechanism is related to repairing BBB integrity remains unclear. This study aims to reveal the mechanism of BBB integrity destruction in DCI mice, and to elucidate the mechanism by which ZSWF repairs BBB integrity and improves cognitive function in DCI mice. Methods Diabetic mouse model was established by feeding a 60% high-fat diet combined with a single intraperitoneal injection of 120 mg/kg streptozotocin (STZ). DCI mice were screened with morris water maze (MWM) after 8 weeks of sustained hyperglycemic stimulation. ZSWF was administered daily at doses of 9.36 and 18.72 g/kg for 8 weeks. Cognitive function was evaluated using MWM, blood–brain-barrier (BBB) integrity was tested using immunostaining and western blot, the underlying mechanisms were explored using single-cell RNA sequencing (scRNA-seq), validation experiments were performed with immunofluorescence analysis, and the potential active ingredients of ZSWF against cerebrovascular senescence were predicted using molecular docking. Moreover, cerebral microvascular endothelial cells were cultured, and the effects of mangiferin on the expression of p21 and Vcam1 were investigated by immunofluorescence staining and RT-qPCR. Results ZSWF treatment significantly ameliorated cognitive function and repaired BBB integrity in DCI mice. Using scRNA-seq, we identified 14 brain cell types. In BBB constituent cells (endothelial cells and pericytes), we found that Cdkn1a and senescence-associated secretory phenotype (SASP) genes were significantly overexpressed in DCI mice, while ZSWF intervention significantly inhibited the expression of Cdkn1a and SASP genes in cerebrovascular cells of DCI mice. Moreover, we also found that the communication between brain endothelial cells and pericytes was decreased in DCI mice, while ZSWF significantly increased the communication between them, especially the expression of PDGFRβ in pericytes. Molecular docking results showed that mangiferin, the blood component of ZSWF, had a stronger affinity with the upstream proteins of p21. In vitro experiments showed that high glucose significantly increased the expression of p21 and Vcam1 in bEnd.3 cells, while mangiferin significantly inhibited the expression of p21 and Vcam1 induced by high glucose. Conclusion Our study reveals that ZSWF can ameliorate cognitive function in DCI mice by repairing BBB integrity, and the specific mechanism of which may be related to preventing cerebrovascular cells senescence, and mangiferin is its key active ingredient. Graphical Abstract